2021
DOI: 10.3390/molecules26247577
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Alpha-Hemolysin as Potential Target to Screen of Flavonoids to Combat Bacterial Coinfection

Abstract: The rapid emergence of bacterial coinfection caused by cytosolic bacteria has become a huge threat to public health worldwide. Past efforts have been devoted to discover the broad-spectrum antibiotics, while the emergence of antibiotic resistance encourages the development of antibacterial agents. In essence, bacterial virulence is a factor in antibiotic tolerance. However, the discovery and development of new antibacterial drugs and special antitoxin drugs is much more difficult in the antibiotic resistance e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The αHL oligomer creates a hemolytic pore in the host cell membrane, which results in a loss of host cell integrity and cell death [ 38 , 39 ]. Recently, it was shown that some flavonoids (e.g., baicalin, kaempferol and quercetin) effectively inhibited the hemolytic activity of S. aureus αHL by modulating the expression of virulence factors [ 40 ]. In our experiments, we have shown for the first time another mechanism of quercetin’s antihemolytic activity, namely the ability to increase the resilience of the erythrocyte membrane to the toxin.…”
Section: Introductionmentioning
confidence: 99%
“…The αHL oligomer creates a hemolytic pore in the host cell membrane, which results in a loss of host cell integrity and cell death [ 38 , 39 ]. Recently, it was shown that some flavonoids (e.g., baicalin, kaempferol and quercetin) effectively inhibited the hemolytic activity of S. aureus αHL by modulating the expression of virulence factors [ 40 ]. In our experiments, we have shown for the first time another mechanism of quercetin’s antihemolytic activity, namely the ability to increase the resilience of the erythrocyte membrane to the toxin.…”
Section: Introductionmentioning
confidence: 99%
“…Natural herbal plants used as feed additives have extensive activities, including antioxidant, immune enhancement, anti-inflammation, etc ( 1 , 2 ). On account of these activities, natural plants have been widely used as feed additives to improve poultry growth and reproductive performance ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, as typical heat-clearing and damp eliminating herbs, Scutellariae Radix has the main flavonoes of baicalein and baicalin using the direct-acting antibacterial activity to fight against MRSA, S. aureus, and Streptococcus suis infections via inhibition of bacterial membrane functions ( Rajkumari et al, 2017 ; Chen et al, 2018 ; Zhang et al, 2020 ; Lu et al, 2021 ) ( Table 1 ). In addition, other flavonoid compounds in heat-clearing herbs also have the antibacterial abilities of damaging the bacterial membrane, such as quercetin from Gardeniae Fructus (iii, heat-clearing and damp eliminating herb) ( Mohamed et al, 2020 ; Yang et al, 2020 ), kaempferol origin from Moutan Coetrx (ii, heat-clearing and blood-eliminating herb) ( Lin et al, 2020 ; He et al, 2021 ), luteolin and lonicerin from Lonicerae Japonica (iv, heat-clearing and toxin-relieving herb) ( Zhang et al, 2018 ; Singh et al, 2021 ), hyperin and hyperoside origin from Lonicerae Japonica (iv, heat-clearing and toxin-relieving herb) ( Rodrigo Cavalcante de Araújo et al, 2019 ), rutin from Forshiae Fructus (iii, heat-clearing and damp eliminating herb) ( Deepika et al, 2019 ; Di Lodovico et al, 2020 ; Motallebi et al, 2020 ), and mangiferin from Anemarrhenae Rhizome (i, heat-clearing and blood-cooling herbs) ( Tchinda et al, 2019 ). These DAC IM flavonoids that treat bacterial strains are detailed in Table 1 .…”
Section: Modes Of Action Of Flavonoids On Resistant Bacteriamentioning
confidence: 99%
“…It is worth noting that quercetin that belongs to flavanols have the inhibitory potential to effectively act as the efflux pump to treat CRNB due to its polyphenol hydroxyl group structure ( Pal and Tripathi, 2020 ). On the other side, flavonoid compounds have the direct-acting antibacterial effect of inhibiting bacterial virulence factors, such as α-hemolysin (Hla) of S. aureus ( Wang et al, 2020 ; He et al, 2021 ). The Hla can cause bacterial entry of host cells and also lead to bacterial coinfection, while flavonoids can target Hla to control bacterial infection ( He et al, 2021 ).…”
Section: Modes Of Action Of Flavonoids On Resistant Bacteriamentioning
confidence: 99%
See 1 more Smart Citation